The Involvement of Mass Organizations (Ormas) in Illegal Levies Practices in West Java - Purwadi, Purwadi; Rifki, M. S.; Hadisaputra, Tomo; Silvana, Leydi (Research and Development Agency Ministry of Home Affairs, 2018)
The Mass Organizations (Ormas) that supposed to contribute to a good, clean government, free of corruption, collusion and nepotism, did exactly the opposite. The Anti-Illegal Levies Raids (OTT) where the alleged perpetrators were caught red-handed by the Anti-Illegal Levies Task Force (Satgas Saber Pungli) involved the mass organizations and thugs. The weak integrity and credibility of Ormas was a major government issue. To that end, the goal of this study was to understand the involvement of Ormas in illegal levies cases in West Java. The method used in this study was the descriptive method with a qualitative approach, Data collection technique was using the interview technique with inductive analysis and purposive sampling. The study found that many unscrupulous organizations pursued illegal levies and that it tended to be difficult to prove, although it massively occurred. Such as corrupted grants, extorted schools, collected illegal levies, demanded Hari Raya (THR) allowances, and exploited the government’s weakness in the Technical Implementation Unit Office (UPTD) of Education. The mass organizations should be registered and monitored as soon as possible to ensure that the problematic organizations can be disciplined.